CHAQ2020 - Snow Hill Island - Photographic and video data - CHAQ2020 - Snow Hill Island - Photographs - Westin, Jonathan; Almevik, Gunnar (University of Gothenburg, 2021)
The first Swedish Antarctic Expedition (1901-1903), led by Otto Nordenskjöld, sailed to Antarctica on the ship Antarctic captained by CA Larsen, and established a research station on Snow Hill Island. There six members overwintered and performed paleontological, meteorological, geomagnetic and geological studies, while the rest of the expedition set sail for South Orkney.

After the winter, on the way back to Snow Hill Island, the Antarctic got stuck in the ice and sank. At this point, the expedition members were divided into three groups. One of these overwintered an extra year on Snow Hill Island, whereas the other two groups were forced to build stone huts in order to overwinter at Hope Bay and Paulet Island. An Argentinean vessel, the Corbeta Uruguay, rescued the expedition in November 1903.

CHAQ 2020 is an Argentinean-Swedish project with fieldwork in the area around the Antarctic Peninsula aiming to investigating and documenting the historical remains of the first Swedish South Polar expedition under the leadership of Otto Nordenskjöld 1901-1903. The material was collected in January and February 2020.

This catalogue entry collects the photographic material, the panoramas, and the drone videos from Snow Hill Island.

The photographs of the remains were shot with several different cameras between January 10-24. Gunnar Almevik’s photographs were shot with a Fujifilm X-T2, Dag Avango’s with a Nikon D800, and Jonathan Westin’s with both an iPhone XR and a DJI Mavic 2 Pro drone.

Syftet med forskningsprojektet var att dokumentera lämningarna efter Otto Nordenskjölds Antarktisexpeditionen 1901-1903. Materialet består av fotografier, planer, ritningar, 3d-modeller och drönarfilmer från Snow Hillön, Hoppets vik och Seymourön.

Denna katalogpost samlar fotografier, panoraman, samt filmer inspelade med drönare, från Snow Hillön.

Se den engelska beskrivningen för mer information.

Fotografierna av lämningarna togs med flera olika kameror 10-24 januari 2020. Gunnar Almeviks fotografier är tagna med en Fujifilm X-T2, Dag Avangos med en Nikon D800, och Jonathan Westins med en iPhone XR samt en DJI Mavic 2 Pro drönare.
CHAQ2020 - Snow Hillön - Fotografiska data och videodata - CHAQ2020 - Snow Hillön - Fotografier
Keywords: Antarctica; Antarktis; Antarctic region; Swedish Antarctic Expedition, 1901-1904; Första svenska Antarktisexpeditionen, 1901-1904; Nordenskjöld, Otto, 1869-1928; Nordenskjöld, Otto, 1869-1928; History and Archaeology; Historia och arkeologi; Structure; Byggnader och byggnadsanläggningar